Enhancing Teacher–Student Interaction and Students' Engagement in a Flipped Translation Classroom - Wei, Yi (Frontiers in Psychology, 2021)
Learning faculties are looking for innovative approaches for effective teaching in the translation process which can not only enhance students’ engagement but also increase the interactions between teacher and learners. With the amplified accessibility of network-centered instructive knowledge, teaching translation from the viewpoint of computer-aided instructions and online platforms are flourished. Flipped classroom (FC) is one of these new inclinations used in higher education nowadays which can attract stakeholders’ attention. This review aims at exploring its effects on students’ engagement and teacher-student interaction in translation classes. Some implications and suggestions have been presented for language teaching stakeholders in translation research.